Comparative Study on the Corneal Endothelial Cell Count between Type 2 Diabetic and Non-Diabetic Patients - AnNasseh, Muhannad Ghazi; Raheem, Saif Ibrahim; Neamah, Giyathaldeen (AL-Kindy College Medical Journal, 2022)
Background: Diabetes mellitus is one of the commonest chronic disorders worldwide with a rapid rise in prevalence. In Iraq its prevalence is high especially in elderly age group. Patients with type 2 diabetes mellitus have higher vulnerability for complications, whether microvascular or macrovascular. Ocular complications are common in diabetes mellitus, and comprise diabetic retinopathy, diabetic papillopathy, cataract, glaucoma, dry eye disease and diabetic keratopathy. Diabetic keratopathy involves endothelial and epithelial tissues of the cornea, leading to persistent epithelial defect, corneal erosion, or corneal ulcers.Aim of the Study: To compare the mean corneal endothelial cell count between patients with type 2 diabetes mellitus and non-diabetics.Subjects and Methods: This is a case-control study conducted in Ibn Al Haitham Teaching Eye Hospital – Baghdad and included 249 participants, 125 cases with type 2 diabetes and 124 controls who had no diabetes. Endothelial cell count was measured for 1 eye of each participant using TOPCON® SP-3000P microscope. Patients who had diabetes for less than 5 years, and patients who had previous ocular surgery, injury or disorders were excluded.Results: There was a significant difference in endothelial cell count between cases with type 2 diabetes mellitus and controls; P = 0.001. There was also a significant negative correlation between age and endothelial cell count, R = -0.20, P = 0.002. Similarly, there was a significant negative correlation between duration of diabetes mellitus and endothelial cell count, R = -0.44, P < 0.001.Conclusions: Type 2 diabetes mellitus causes significant reduction in mean corneal endothelial cell count. There is also a negative correlation between corneal endothelial cell count and both age and duration of the disease.